Arginine-mediated inhibition of macrophage apoptosis by Escherichia coli nissle 1917 in Salmonella typhimurium-induced intestinal inflammation - Zhang, Lu; Yang, Jiahui; Shi, Qixue; Chu, Yanyan; Cao, Jiarui; Shang, Chenglong; Zhou, Changlin; Ma, Lingman (Frontiers in Immunology, 2025)
IntroductionIntestinal inflammation is a chronic, relapsing disorder of the gastrointestinal tract characterized by dysregulated immune responses, microbial dysbiosis, and environmental influence. Pathogen clearance is related to the severity of intestinal diseases and macrophage apoptosis. Escherichia coli Nissle 1917 (EcN) alleviates the intestinal inflammation caused by Salmonella enterica serotype Salmonella Typhimurium (Salmonella Typhimurium, S. Tm) infection.MethodsThrough gene editing, we found that the regulatory gene arcA largely affects arginine production in EcN via the arginine deiminase pathway. In vitro studies demonstrated that EcN alleviates S. Tm-induced apoptosis in RAW264.7 cells by enhancing intracellular arginine levels. Specifically, arginine generated by EcN can reduce S. Tm infection-induced generation of reactive oxygen species (ROS), chromatin condensation, DNA fragmentation, disruption of plasma membrane integrity, and decrease in mitochondrial membrane potential. Additionally, arginine administration in S. Tm-challenged mice decreased bacterial burden in the gut, suppressed Caspase-3 (CASPASE3) activation, mitigated both inflammation and apoptosis, and maintained epithelial barrier.Result and discussionMechanistically, arginine suppresses S. Tm-driven B-cell lymphoma-2 (BCL2) downregulation, inhibiting apoptosis. Further analysis revealed that arginine may disrupt the interaction between ribosomal protein S3 (RPS3) and serine/serine and arginine rich splicing factor 3 (SRSF3), thereby further suppressing the expression of apoptosis-related proteins induced by S. Tm. Our research offers new targets and approaches for treating bacterial infection-induced intestinal inflammation.